Ecological Index and Conservation Status of Bird (Avifauna) Species in Gunaksa Village and Several Surrounding Areas in Klungkung Regency, Bali - Wijana, I Made Sara; Wijaya, I Made Saka; Syahputra, M. Rheza Rizki; Widiyavedanta, Gde Oka; congdenjit, Egmont; Indrawan, Gede Surya; As-syakur, Abd. Rahman; Wiradana, Putu Angga (Metamorfosa: Journal of Biological Sciences, 2021)
The Gunaksa Village and several surrounding areas in Klungkung Regency, Bali have the potential to be developed as one of the international ecotourism destinations in Indonesia. This study aims to determine the diversity and status of bird species (avifauna) in the Gunaksa Village Area and several surrounding areas so that it is expected to be the basis for information on natural resource management in this area. The method used is the "Cruise method", which is tracing paths that can be used to represent various types of ecosystems in the research area. The results showed that 46 species of birds were obtained with the highest Relative Abundance Index (RAI) value obtained by the buffalo egret (Bubulcus ibis) of 9.50% (dominant). The ecological index of bird species shows a high category in the Diversity Index (H') (3.16), Richness Index (R) (7.15), and Evenness Index (E) (1.87). Species of the black-winged kite, Javan ermine, Christmas frigatebird, and Pied fantail are protected species based on the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number p.106/menlhk/setjen/kum.1/12/2018, while only the frigatebird Christmas is included in the IUCN RedList with the Critical (CR) category. Conservation efforts and the participation of government agencies, academics, practitioners and the community are needed to increase the environmental awareness of the Gunaksa area and its surroundings for the sustainability of Avifauna in the area.